Media as a Tool for Preventing Corruption in the Sphere of Attracting Private Investment in the Republic of Kazakhstan - Zagrebin, A.; Davletbayeva, Zh.; Davletbayeva, N. (BUKETOV BUSINESS REVIEW, 2024)
Object: To study the role of the media in preventing corruption risks in the sphere of attracting private investment in the Republic of Kazakhstan, their effectiveness in the anti-corruption campaign. Methods: A content analysis of publications in the news media about corruption offenses in the implementation of private investment projects was carried out using the Google Search tool through search queries using key phrases. Findings: The results of the content analysis demonstrate the insufficient use of the potential of the Kazakh media in the issue of preventing corruption. The number of news messages with a negative connotation is only 18.7 % of the total sample, while messages with a positive and neutral background are prevalent. This can be explained by the control of online news publications by government agencies, their politicization and the lack of independent journalistic initiative in the Republic of Kazakhstan. Conclusions: Taking into account the world practice of using the media as an institution of public control and prevention of corruption offenses, recommendations are made to improve the process of involving Kazakhstani media resources in this activity.